1994
DOI: 10.1111/j.1748-5827.1994.tb03823.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary treatment of progressive feline struvite crystalluria

Abstract: Eight cats were fed a dry commercial cat food and after six months developed urinary struvite crystalluria with alkaline urine. The animals were subsequently divided into two groups and fed either a dry or a canned struvite calculolytic diet. The crystalluria was reduced after five to six weeks with both treatment diets. Decreased crystalluria coincided with a reduction in urinary pH and an increased titratable acidity. The highest food acid load, determined by the lowest undetermined anion, was found with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…22 However, our observations are similar to other studies 13,[39][40][41] in which struvite crystalluria was observed in cats fed low-magnesium, urine-acidifying foods. When present, struvite was the predominant crystal type observed in urine sediment from both cats fed prevention food and cats fed control food; calcium oxalate crystalluria was not observed in cats of either food group.…”
Section: Discussionsupporting
confidence: 92%
“…22 However, our observations are similar to other studies 13,[39][40][41] in which struvite crystalluria was observed in cats fed low-magnesium, urine-acidifying foods. When present, struvite was the predominant crystal type observed in urine sediment from both cats fed prevention food and cats fed control food; calcium oxalate crystalluria was not observed in cats of either food group.…”
Section: Discussionsupporting
confidence: 92%
“…Moist foods are known to reduce urine concentration of urolith-forming metabolites. 6 The observed reversal of the effect of moisture content of diet is unclear. Possibly, dry diets could be a predisposing factor for HSC up to a stage in life.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, nearly 30% of cats with struvite crystalluria experience hematuria due to the irritation of the bladder walls by the crystals. 6 Therefore, an evaluation of the presence of struvite crystals in the urine of cats with hematuria could provide useful information in our understanding of these common condition in cats.…”
Section: Introductionmentioning
confidence: 99%
“…Gevaert et al proposed that large numbers of crystals could be irritating to the bladder wall, after inducing marked struvite crystalluria in eight healthy cats by feeding them a commercial dry cat food and observing haematuria, proteinuria and weight loss in two of the treated cats; both the crystalluria and clinical signs in these cats resolved with feeding of a calculolytic diet. 24 In an experimental rodent model, induction of heavy crystalluria in rats was associated with hyperreflexiveness of the micturition reflex, a result that investigators hypothesised was an effect of crystals on the bladder mucosa. 25 In human medicine, administration of the anti-retroviral drug indinavir can induce a marked crystalluria that has been associated with back pain, with and without urolithiasis.…”
Section: Discussionmentioning
confidence: 99%